2021
DOI: 10.7150/thno.56936
|View full text |Cite
|
Sign up to set email alerts
|

An “eat me” combinatory nano-formulation for systemic immunotherapy of solid tumors

Abstract: Rational: Tumor immunogenic cell death (ICD), induced by certain chemotherapeutic drugs such as doxorubicin (Dox), is a form of apoptosis potentiating a protective immune response. One of the hallmarks of ICD is the translocation of calreticulin to the cell surface acting as an 'eat me' signal. This manuscript describes the development of a stable nucleic acid-lipid particles (SNALPs) formulation for the simultaneous delivery of ICD inducing drug (Dox) with small interfering RNA (siRNA) knocking dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 61 publications
0
41
0
Order By: Relevance
“…Although DOX is not the most sensitive chemotherapy agent for prostate cancer, it is the most widely used immunogenic death stimulant ( 17 ). It certainly promotes ICD, a well-defined type of apoptotic process ( 47 ). Released DAMPs can be recognized by pattern recognition receptors (PRRs) and induce antigen-presenting cells(APC) to activate, differentiate, and mature ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although DOX is not the most sensitive chemotherapy agent for prostate cancer, it is the most widely used immunogenic death stimulant ( 17 ). It certainly promotes ICD, a well-defined type of apoptotic process ( 47 ). Released DAMPs can be recognized by pattern recognition receptors (PRRs) and induce antigen-presenting cells(APC) to activate, differentiate, and mature ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…ICD has a number of clearly defined physiological characteristics, including cell surface CRT expression, release of DAMPs such as adenosine triphosphate and heat shock proteins, and release of high mobility group box 1 ( Liu et al, 2016 ). Among these factors, the surface expression of CRT is considered to be the single most important element of ICD ( Abdel-Bar et al, 2021 ). As previously mentioned, the effect of CRT exposure, serving as an “eat me” signal, is considered to be counterbalanced and potentially dampened by CD47 expression ( Chao et al, 2010a ).…”
Section: Role Of the Cd47-sirpα Checkpoint In Nanomedicine-based Dise...mentioning
confidence: 99%
“…Moreover, the upregulated expression of CD47 on the surface of tumor cells makes it an active targeting site for tumor cells, facilitating nonspecific distributed ICD inducing drugs to target tumor tissues and reduce systemic toxicity ( Tang et al, 2021 ). Therefore, codelivery, which simultaneously removes an inhibitory signal and introduces an activating signal, can produce an enhanced antitumor effect ( Abdel-Bar et al, 2021 ; Lee et al, 2021 ). For example, Abdel-Bar et al reported a stable nucleic acid-lipid particle (SNALP) formulation with the simultaneous delivery of an ICD inducing drug (Dox) with small interfering RNA (siRNA) knocking down CD47 (siCD47) for synergistic enhancement of ICD.…”
Section: Role Of the Cd47-sirpα Checkpoint In Nanomedicine-based Dise...mentioning
confidence: 99%
See 1 more Smart Citation
“…[18] Tumor cells undergoing ICD trigger to release calreticulin (CRT) and high-mobility group box 1 (HMGB1) to promote DC maturation and activate antigen-specific T cell responses. [19] However, the ICD-induced therapeutic effect is severely abolished by negative immune regulation mechanisms. [20,21] Furthermore, the poor pharmacokinetics of these drugs limit their widespread use in cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%